ASPEK ERGONOMI DALAM DESAIN KAMAR MANDI MODERN - Siti Badriyah (Institut Seni Indonesia Surakarta, 2012)
Perhaps many of us who like to spend some time in the bathroom. In the midst of a crowded for some people, relaxing in the bathroom when the home office to be very enjoyable and a relaxation therapy activities. For that atmosphere of support and comfort is a factor that can not be dipisahkan.Salah a supporting factor is comfort ergonomic factors in the design of a bathroom is very important factor ergonomic comfort when his bathroom into a demand not just routine cleaning the body only. Ergonomics of human is a key part of a system (Human Integrated Design), it must be recognized correctly that the human factor will be the key determinant of success in the design of a modern bathroom that is functional, comfortable, pleasant and aestheticallyKeyword: ergonomic, bathroom